Asteroseismic Characterization of 142 Solar-like Oscillators Hosting Confirmed Exoplanets - Wen-Xu Lin; Sheng-Bang Qian; Li-Ying Zhu; Fu-Xing Li; Qi-bin Sun; Wen-Ping Liao; Ping Li; Xiang-Dong Shi; Ting Li (The Astrophysical Journal Supplement Series)
We present the largest catalog of exoplanet host stars with solar-like oscillations compiled to date, providing a powerful resource for refining stellar and planetary characterization via asteroseismology. By combining high-precision photometric data from Kepler and the Transiting Exoplanet Survey Satellite with the automated pySYD pipeline, we systematically searched thousands of confirmed host stars for solar-like pulsations. From this process, we identified 174 stars displaying distinct oscillatory signatures, of which 142 offered sufficiently high signal-to-noise ratios and frequency resolution. For these 142 targets, we derived global stellar parameters—such as mass, radius, and surface gravity—confirming consistency with published spectroscopic data. This synergy between asteroseismic and spectroscopic methods fosters robust constraints on stellar properties and enables more accurate planetary analyses, while also highlighting the value of long-baseline photometry for probing stellar interiors and bridging observational gaps across various evolutionary phases. We additionally draw attention to 32 host stars that exhibit low-frequency pulsations but remain only partially characterized, primarily due to their large radii or limited observational baselines. These systems underscore the potential for future observations to explore interactions between planets and giant host stars, as well as broader implications for planetary evolution. Altogether, the curated stellar parameters and asteroseismic data establish a foundation for deeper investigations into planetary system architectures and the long-term evolution of exoplanets under varying stellar conditions.